نظام التكاليف المعيارية كأداة لتقويم الأداء في البيئة التصنيعية الحديثة - دراسة حالة- - فخر, نواف; شيخ محمد, حسين; جديد, غيث محمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يعتبر نظام التكاليف المعيارية صورة متقدمة من أنظمة التكاليف المحددة مقدماً, وأداة إدارية هامة تساعد على توجيه قرارات الإدارة, ورفع مستوى كفاءة الأداء في الوحدة الاقتصادية, والرقابة على عناصر الإنتاج لتحقيق أعلى مستوى ممكن من الكفاية في استخدام هذه العناصر, والوصول إلى قياس عادل ودقيق لتكلفة المنتجات. وتُمثل مؤشرات تقويم الأداء مجموعة من المقاييس المالية وغير المالية اللازمة للحكم على مدى تقدم الوحدة الاقتصادية نحو تحقيق الأهداف الإستراتيجية العامة والفرعية, وتعكس مدى التحسين المستمر لمنتجاتها, وتدعم القدرة التنافسية لتلك المنتجات في الأسواق المحلية والدولية. وهنا يتناول الباحث نظام التكاليف المعيارية في ظل المتغيرات البيئية الحديثة والمتمثلة في عالمية المنافسة وتكنولوجيا التصنيع الحديثة, ولتحقيق الهدف من البحث قام الباحث بإعداد استبانة شملت /14/ فقرة وزعت على /55/ عاملاً في شركة مصفاة بانياس, ومن ثم تم تحليل البيانات باستخدام البرنامج الإحصائي SPSS, وتم التوصل إلى مجموعة من النتائج أهمها: يحقق نظام التكاليف المعيارية للشركة أهداف متعددة في البيئة التصنيعية الحديثة. تستخدم الشركة مؤشرات مالية وغير مالية لتقويم الأداء, ويتم إعدادها بشكل دوري وفوري لكل مستوى إداري ولكل مركز تكلفة. لا بد من تطوير نظام التكاليف المعيارية في ضوء التكلفة المستهدفة بحيث يعكس متغيرات السوق والبيئة التنافسية. Standard costing system is considered an advanced form of the predetermined costing systems, and an important administrative tool that directs the administration decisions, and enhances the performance in the economic enterprise. It additionally helps in controlling the production elements to achieve the highest level of sufficiency in using these elements, and arriving to an exact and equitable measurement of products cost. Performance evaluation measures is a group of financial and non financial measures for verdict to progress the enterprise side realization the public and secondary strategic aims, and it reflects the continuous improvement to its products, and it supports the competitive ability of those products in the international and national markets. And for realizing the aim from the research, the researcher prepared a questionnaire including /14/ paragraphs, which were distributed to /55/ workers in company of Banias refinery, and the data were submitted to analysis by using statistics program to sociology sciences, and the research reaches a series of results, the most important ones are: Standard costing system has realized numerous aims to company in the new industrial environment. The company uses financial and non financial measures to perform evaluation, and it prepares periodically and immediately for every administrative level and cost center. It is necessary to develop the standard costing system through the target cost, which reflects variables of market and competitive environment.